The Properties and Fracture Behavior of Ion Plasma Sprayed TiN Coating on Stainless Steel Substrate; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Orlova D. V. Dina Vladimirovna; Goncharenko I. M. Igor Mikhailovich; Danilov V. I. Vladimir Ivanovich; Lobach M. I. Maxim; Danilova L. V. Lidiya; Shlyakhova G. V. (2015, 2015)
Title screen